Processamento sensorial, qualidade de vida e fatores associados ao transtorno do desenvolvimento da coordenação em escolares - Weber, Meyene Duque (2024)
Introduction: Developmental Coordination Disorder (DCD) is characterized by significant motor performance difficulties. Mechanisms that may contribute to the etiology of DCD include alterations in sensory processing. Additionally, the presence of risk factors, whether biological or environmental origin, may exacerbate motor difficulties during childhood. Beyond the primary motor problems associated with DCD, secondary issues frequently arise, particularly socioemotional and psychological consequences such as a reduced health-related quality of life (HRQoL). Objective: To assess sensory processing and quality of life in children with Developmental Coordination Disorder, as well as potential contextual factors associated with children with and without DCD. Methodology: This is a case-control study conducted in schools within a small city in the state of São Paulo, Brazil. Participants included children of both sexes, aged between 6 and 11 years, along with their parents/guardians. The children were divided into three groups according to the diagnostic criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5 TR): the DCD group (case group one) consisted of children who met all four diagnostic criteria; the probable DCD group (case group two) included children who met two diagnostic criteria; and the typical development group (control group) consisted of children with motor performance appropriate for their age and no established diagnoses. The children were assessed using the following instruments: the Movement Assessment Battery for Children – 2nd edition, the DCD Questionnaire, the Sociodemographic Questionnaire, the Short Sensory Profile 2, and the Pediatric Quality of Life Inventory version 4.0. All statistical tests were performed using SPSS, with a significance level of 5% (α = 0.05). Results: This research yielded three main studies: Study I, entitled "Sensory processing in children with Developmental Coordination Disorder, probable DCD, and typical development: a case-control study," found significant differences among the groups in all four sensory processing patterns, with a higher frequency of sensory registration patterns in the DCD group. Furthermore, the sensory registration pattern emerged as a predictor of motor outcomes. Study II, titled "Health-related quality of life in children with Developmental Coordination Disorder: a systematic review," showed that children identified with DCD had poorer HRQoL compared to their typically developing peers. Study III, titled "Health-related quality of life in children with Developmental Coordination Disorder, probable DCD, and typical development: what is the relationship with environmental and biological factors?" revealed significant differences in HRQoL scores among the groups, with children with DCD showing the lowest scores. Biological and environmental risk factors, such as prematurity and low socioeconomic status, were detrimental to HRQoL when interacting with the groups. Conclusion: The findings contribute to the growing body of evidence regarding children with DCD and probable DCD, providing novel insights into how the studied variables behave across the three groups. Specifically, children with DCD exhibit poorer outcomes in sensory processing and HRQoL. Moreover, children with DCD, when associated with risk factors, experience a further decline in HRQoL. These findings offer valuable information to healthcare and education professionals, enabling them to act as key agents in knowledge translation for families and individuals affected by DCD.